Socio-dynamics information space as an object of scientific research - Sidorskaya, Iryna V. (Journal of the Belarusian State University. Journalism, 2019)
The paper considers the main theoretical and methodological approaches to the problem of socio-dynamics of the information space. It analyses the factors and drivers of the evolution of the information space as identified by national and Russian researchers. The paper proposes a new approach to the evolution of the information space based on the interpenetration  and interaction of its main subsystems, mainly journalism, PR and advertising. The paper argues that both the nonclassical (system approach) and postclassical methodologies are meaningful tools for the analyses of the information space. It argues  that the idea of plurality of potential states of the system in the synergetic paradigm is consonant to the projective character of public relations. The paper also substantiates the idea of primarily internal prerequisites for the evolution of modern information space, first of all those linked to the emergence of new levels of its organisation. The paper argues that new conceptual approaches that will allow for the interpretation of the specificity of the evolution of information space under the influence of exogenous factors derived from the internal process of interaction of different subsystems needed to be developed.
Keywords: information space; systems approach; synergetic approach; public relations (PR)